2018
DOI: 10.1590/2175-8239-jbn-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

APOL1 risk variants and kidney disease: what we know so far

Abstract: There are striking differences in chronic kidney disease between Caucasians and African descendants. It was widely accepted that this occurred due to socioeconomic factors, but recent studies show that apolipoprotein L-1 (APOL1) gene variants are strongly associated with focal segmental glomerulosclerosis, HIV-associated nephropathy, hypertensive nephrosclerosis, and lupus nephritis in the African American population. These variants made their way to South America trough intercontinental slave traffic and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 98 publications
1
18
2
2
Order By: Relevance
“…The incidence and prognosis of HIVAN and HIVICK among HIV patients in Colombia and in Latin America is unknown. It could be different to the prognosis described in other countries as the APOL1 polymorphism in the region is very low compared with populations in Europe, North America and Africa [9,10].…”
Section: Introductioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The incidence and prognosis of HIVAN and HIVICK among HIV patients in Colombia and in Latin America is unknown. It could be different to the prognosis described in other countries as the APOL1 polymorphism in the region is very low compared with populations in Europe, North America and Africa [9,10].…”
Section: Introductioncontrasting
confidence: 69%
“…Furthermore, the patients included in Post and Bigé cohorts were predominantly African descendants [approximately 90%], a population that has been associated to worse outcomes [18], related to the apolipoprotein L-1 (APOL1) gene variants [19], a polymorphism that has not been found in Latin American populations [9].…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion might be biologically plausible, as APOL1 is a major apo component of HDL3 particles, which plays a key role in cholesterol transport and the limitation of low-density lipoprotein (LDL) oxidation [138]. These two APOL1 alleles are also associated with a higher incidence of CKD (including focal segmental glomerulosclerosis, collapsing glomerulopathies, and arterionephrosclerosis) and a more progressive course of the disease in the African American population [2,139,140]. The Jackson Heart Study demonstrated a two-fold increase in the risk of cardiovascular events in carriers of high-risk genotype (G1/G1, G2/G2, or G1/G2).…”
Section: Cardiovascular Risk Related To Modifications Of Hdl Particlementioning
confidence: 99%
“…Chronic kidney disease (CKD) is a worldwide health problem with occurrence steadily increasing by approximately 6% annually, and significant differences in prevalence between populations [1,2]. According to the analysis performed for the Global Burden of Disease Study 2010, CKD-associated mortality almost doubled between 1990 and 2010; at the end of 2013, over three million people worldwide were undergoing renal replacement therapy (RRT), including two and a half million on hemodialysis or peritoneal dialysis, and nearly 700,000 who had received a kidney transplant [2,3]. Current estimations (2019) concerning the US population indicate that 15% of US adults (37 million people) have CKD [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation